Restoration and wear resistance of electric transport sliding contacts - Kovtun, O.S.; Dytyniuk, V.O.; Staryi, A.L.; Fasolia, V.O. (Problems of Tribology, 2024)
The electrical contact insert of the current-carrying suspension of the electric vehicle belongs to the fast-wearing elements that require frequent replacement and attention to ensure standard performance. The purpose of this study was to develop a technology for manufacturing graphite-filled electrical contact inserts from waste materials and by modifying the composition of the composite. As a result of difficult operating conditions, coal current collector inserts of electric transport are subject to considerable wear. The causes of increased wear are electrocorrosion in contact with the conductor under current, abrasive wear from sliding on the wire with increased dustiness and air humidity. The technological process of manufacturing graphite current-collecting inserts from used graphite components is proposed. To prove the functionality of the restored current-collecting inserts, the strength, electrical conductivity and tribological characteristics of the material were tested. The results of experimental tests showed a slight decrease in material hardness and an increase in electrical resistance within acceptable limits. Bench wear tests showed improved tribological properties of the restorative insert material with the addition of copper powder.